Antibiotic Evaluation Use towards Diabetic Foot Ulcer Inpatient at Hospital in Surakarta - Lilla Prapdhani Agni Hajma; Hidayah Karuniawati; Nurul Mutmainah (Universitas Muhammadiyah Surakarta, 2022)
A diabetic foot ulcer is one of diabetes mellitus type 2 complications indicated by open sores. Because it contains bacteria, it is treated with antibiotics. Improper use of antibiotics could harm patients due to the length of wound healing. This study aims to determine the appropriate of antibiotics in patients with a diabetic foot ulcers. This is a non-experimental research with descriptive analysis approach. The medical records of diabetic foot ulcer patients undergoing inpatient and antibiotic prescribing are observed. The data obtained were analyzed by comparing the use of antibiotics based on the National Health Service guidelines, the Indonesian National Drug Information, and the Drug Information Handbook. The results of this study showed antibiotics used are metronidazole (4.8%), vancomycin (4.8%) and antibiotics combination are ceftriaxone-metronidazole (47.6%), ceftriaxone-metronidazole-clindamycin (4,8%), levofloxacin-azithromycin-ceftriaxone (4.8%), cotrimoxazole-ciprofloxacin (4.8%), metronidazole-meropenem (4.8%), ceftriaxone-metronidazole-gentamicin (4.8%), metronidazole-clindamycin-ciprofloxacin (4.8%), ceftriaxone-levofloxacin (4.8%), and ceftriaxone-metronidazole-ciprofloxacin (9.5%). The evaluation results according to criteria appropriate usage of antibiotics that is 100% appropriate indication, 100% for appropriate of patients, 42.3% for appropriate drug, and 61.9% for the appropriate dose.